GUGUSAN PEMIKIRAN DAN IDEOLOGI HADRATUSSYAIKH UNTUK BANGSA DALAM KITAB HADIS ARABAIN KH. HASYIM ASY’ARI - Friyadi, Arif (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2023)
This paper reveals that the reaffirmation of Nusantara Islam is a response to the issue of disintegrity that has hit several Islamic countries, especially the Middle East. What Ritchey and Muchtar did provides evidence that the yellow book (turats) has contributed greatly to the moderation of Islam in Indonesia. Because of that, in the last decade there has been a call to dig up scientific treasures from the books of Indonesian scholars. From the various Arba'in hadith books above, the genealogy of the network of hadith chains from Hadratus Shaykh Hasyim Asy'ari is a long-standing research to study. Hadith research Arbain KH. Hasyim is considered very important because he can reveal the veil of advice implied in 40 hadiths. The clusters of thought include efforts to unite the nation and respect the differences of the ummah as well as the basic foundation for the establishment of the NU organization, the largest Islamic organization in Indonesia. This study used a qualitative library research method, which is a series of research activities that are closely related to the method of collecting library data. The results of the research are expected to foster a sense of community unity in facing the challenges of this nation's disintegrity.